Does STEM-project based learning improve students' literacy as scientific competencies? - Saidaturrahmi, Intan; Susilo, S; Amirullah, Gufron (Biosfer: Jurnal Pendidikan Biologi, 2021)
Twenty-first-century skills impact educational reform centered on science, technology, engineering, and mathematics (STEM). Middle schools specifically apply STEM to improve students' science skills. Several literature studies show the success of STEM in improving student competence. The effect of STEM-PjBL on the science competencies of grade X students will be specifically explored in this study. The sample consisted of 60 high school students divided into an experimental class (n=30) and a control class (n=30). The posttest-only control group design was adopted in this study. STEM-PjBL learning with reproductive system material was implemented in the experimental class (n = 30) for two weeks, and lecture model learning was implemented in the control class. A total of 60 randomly selected high school students were involved in this study. Quantitative data were processed using Microsoft Excel. Hypothesis testing with normality and homogeneity tests was followed by a t-test because the data were normally distributed and homogeneous. This study reveals: (1) The STEM-PjBL model affects student competence. (2) In practical-based materials, the integration of STEM in PBL is proper. (3) Based on the analysis of the STEM-PjBL instrument, the experimental group outperformed the control group on the post-test results. Learning with the systematic STEM-PjBL model has a significant influence on students' science competence.